Has the environment changed - what can be done to help the fishermen community? the views of the small scale fishermen in Malaysia - Idris, Khairuddin; Muhammad, Mahazan; Abu Samah, Asnarulkhadi; Suandi, Turiman; Mohamed Shaffril, Hayrol Azril (Universiti Putra Malaysia Press, 2018)
The inconsistencies among findings and lack of related studies have led to this study, the main objective of which is to gain the views of Malaysian small-scale fishermen on environmental changes and to recommend several strategies that can assist the fishermen community in coping with changes. This study is qualitative in nature. A total of three FGDs and one in-depth-interview were conducted among small-scale fishermen. Based on the thematic analysis, their awareness of environmental changes, the causes of environmental changes, the impact of these changes on the community and measures taken to absorb this impact have been identified. A number of recommendations related to providing alternative skills, conducting research, encouraging proactive roles by influential persons, using fisheries technology, conducting extra monitoring activities and making conservation efforts are highlighted.